2011
DOI: 10.1111/j.1439-0272.2011.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of premature ejaculation by glans penis augmentation using hyaluronic acid gel: a pilot study

Abstract: Premature ejaculation (PE) is by far the most common male sexual complaint, with millions of men affected all over the world. It is estimated that up to 20-30% of all men may be suffering from various forms of PE. A variety of filler materials are widely used nowadays for soft tissue augmentation. The appropriate filler can restore symmetry, volume and create a smooth skin surface The aim of this pilot study was to evaluate the therapeutic effect of hyaluronic acid gel injection in patients with PE. Sixty men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 9 publications
5
39
0
3
Order By: Relevance
“…1, 2 A definition of PE has not been standardized yet 3 because of the large and controversial debate surrounding this term. However, in medical practice, this term is commonly defined as ‘the ejaculation that regularly occurs at or around initial vaginal penetration', 4 and it is not the result of a prolonged absence from sexual activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 2 A definition of PE has not been standardized yet 3 because of the large and controversial debate surrounding this term. However, in medical practice, this term is commonly defined as ‘the ejaculation that regularly occurs at or around initial vaginal penetration', 4 and it is not the result of a prolonged absence from sexual activity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Filler materials have been extensively used for soft tissue augmentation in aesthetic surgery, but it is only recently that they have found an important application in the field of glans penis augmentation allowing to achieve a volume sufficient to prevent PE. 2, 6 Abdallah et al 2 evaluated the effect of hyaluronic acid in 60 men affected by PE, demonstrating that intravaginal ejaculation latency time (IELT) increased 1 month after the injection of the compound in their penis. Furthermore, in 2008, another study 6 reported positive results in a 5-year long-term study in which hyaluronic acid gel was injected in 38 men.…”
Section: Introductionmentioning
confidence: 99%
“…If the outcome is solely based on the results of observational studies, as observed in the HA gel literature to date, a vulnerable methodology makes it difficult to decipher between what is the result of treatment, and the result of faulty associations. As an example, while the previously described HA gel treatment 5-year follow-up study showed no difference in IELT when compared to immediate post-op IELTs, a more recent pilot study from 2012 documented that the IELT had dropped from 7.71 min post-op to 5.32 min after just three months, demonstrating need for follow-up (8). Additionally, similar to the previous argument against the results with DNN, all studies for HA gel augmentation was conducted in single center institutions, and with a relatively small sample size.…”
Section: Surgical Therapy Overviewmentioning
confidence: 99%
“…Complications are very rare and easily manageable by expert surgeons (Littara et al, 2013). Filler materials have shown an important role in the field of glans penis augmentation and was found to prevent PE (Kwak et al, 2008;Abdallah et al, 2012). Hyaluronic acid injection can be effectively used for treatment of PE allowing an increase in IELT.…”
Section: Hyaluronic Acidmentioning
confidence: 99%